2019
DOI: 10.1109/access.2019.2923836
|View full text |Cite
|
Sign up to set email alerts
|

A High-Precision Hybrid Analog and Digital Beamforming Transceiver System for 5G Millimeter-Wave Communication

Abstract: In this paper, the development of a millimeter-wave hybrid beamforming (HBF) transceiver system for 5G millimeter-wave multiple-input-multiple-output (MIMO) communication is presented. The developed transceiver system is operated at 28-GHz band in the time division duplex (TDD) mode, with 500-MHz signal bandwidth. To implement high beamforming accuracy, a phased-array-based HBF transceiver with high-precision phase shifting network (PSN) at intermediate-frequency (IF)-paths is proposed. The designed PSN has 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
(31 reference statements)
3
26
0
1
Order By: Relevance
“…In both works, the MUSIC algorithm is applied in the reconstructed snapshots to estimate the unknown AoAs. It is pointed out, here, that, differently to [22] and more recent works [6], [25], [26] and [27] this paper summarizes and extends previous findings providing an alternative approach to the problem. Specifically, unlike previous works which focus on new AoA estimation techniques, in this work the key idea is to develop techniques which, based on the sampled output of a hybrid array, will reconstruct the snapshots that would have been captured using a conventional (non-hybrid) ULA.…”
Section: Introductionsupporting
confidence: 71%
“…In both works, the MUSIC algorithm is applied in the reconstructed snapshots to estimate the unknown AoAs. It is pointed out, here, that, differently to [22] and more recent works [6], [25], [26] and [27] this paper summarizes and extends previous findings providing an alternative approach to the problem. Specifically, unlike previous works which focus on new AoA estimation techniques, in this work the key idea is to develop techniques which, based on the sampled output of a hybrid array, will reconstruct the snapshots that would have been captured using a conventional (non-hybrid) ULA.…”
Section: Introductionsupporting
confidence: 71%
“…In both works, the MUSIC algorithm is applied in the reconstructed snapshots to estimate the unknown AoAs. It is pointed out, here, that, differently to [23] and more recent works [6], [26], [27] and [28], this paper summarizes and extends previous findings, providing an alternative approach to the problem. Specifically, unlike previous works which focus on new AoA estimation techniques, in this work, the key idea is to develop techniques which, based on the sampled output of a hybrid array, will reconstruct the snapshots that would have been captured using a conventional (non-hybrid) ULA.…”
Section: Introductionsupporting
confidence: 68%
“…Also, in addition to mitigating path loss, high-directivity reference signaling in mmWave beamforming can provide an assist with scattered signals such that the non-line-of-sight links can also be leveraged. An example of a high-directivity practical beamformer at 28 GHz, which provides high accuracy and precise phase shifting is given in [28] (see Figure 10.5(a)). While an evaluation study on a beamforming (receiver) array is shown in Figure 10.5(b) with digital baseband processing given in [34] wherein accurate phase shifting in a large-scale array is evaluated ( Figure 10.6).…”
Section: Hybrid or Analog/digital Beamformersmentioning
confidence: 99%
“…While an evaluation study on a beamforming (receiver) array is shown in Figure 10.5(b) with digital baseband processing given in [34] wherein accurate phase shifting in a large-scale array is evaluated ( Figure 10.6). Both systems in [28,34] are implementable with reference signaling [36] for mmWave channel estimation.…”
Section: Hybrid or Analog/digital Beamformersmentioning
confidence: 99%
See 1 more Smart Citation